Pengaruh Lingkungan Sekolah Dan Motivasi Belajar Terhadap Hasil Belajar Siswa Pada Mata Pelajaran IPS Kelas VIII di Uptd SMP Negeri 1 Pematang Siantar - Frans Baren Einstein Napitupulu; Injen Pardamean Butar Butar; Herlina Hotmadinar Sianipar (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This research aims to determine the influence of the school environment and learning motivation on student learning outcomes in class VIII social studies at UPTD SMP Negeri 1 Pematang Siantar. The variables in this research are the school environment and learning motivation as the independent variable and learning outcomes as the dependent variable. This type of research is associative research with a quantitative descriptive data analysis approach, with a research population of all class VIII IPS students at SMP Negeri 1 Pematang Siantar and a research sample of students from class VIII IPS at SMP Negeri 1 Pematang Siantar consisting of 187 students selected using simple random sampling. (Slovin's formula). Data collection techniques used instruments: (1) school environment questionnaire, (2) learning motivation questionnaire, and (3) learning outcomes in the form of mid-semester test scores. The results of this research show that: (1) there is a positive and significant influence of the school environment on learning outcomes. This result can be seen in the t test where the t value of the school environment (6.11) > t table value (1.660) which means that this variable is significant. (2) there is a positive and significant influence of learning motivation on learning outcomes, this result can be seen in the t test where the calculated t value of learning motivation (7.65) > t table value (1.660) which means that this variable is significant. (3) the school environment and learning motivation jointly influence learning outcomes, this result can be seen in the F test where the Fcount value (6.85) > compared to the Ftable value (1.660). The R Square coefficient of determination test was found to be 0.2809, which means that 28.9% of school environment variables and learning motivation influence student learning outcomes at SMA Negeri 2 Pematang Siantar and the remaining 71.1% is the influence of other variables not examined in the research. This.